Perancangan dan Implementasi Iqra Braille Elektronik Berbasis Mikrokontroler dan Android - Hidayat Hidayat; Boni Al Amin (Komputika : Jurnal Sistem Komputer, 2017)
Braille codes are letters that are known by blind people to be able to obtain information through books including the Qur'an. The availability of media to learn to read the Qur'an in Braille code for blind people is very limited. In addition, the availability of teachers of the Koran for the blind is very limited because not many people can see normally who understands the Qur'anic letters in Braille code, so it is necessary to design and implement an Iqra Electronic Braille device to facilitate the reading process. the Qur'an in Braille code for blind people. One of the Koran learning methods applied in this design is the Iqra method. This device consists of two parts, namely a device for teachers / instructors in the form of an android application and a device for students / blind people who will learn in the form of electronic devices Braille cell viewers using piezoelectric mechanics. Communication between the Teacher's device and the Student's device uses wireless communication media, namely Bluetooth. The Iqra electronic device for the visually impaired is expected to facilitate teachers to teach blind people to read the Qur'an in the Braille code using the Iqra method as an effort to reduce the illiteracy of the Qur'an, especially blind people. Keywords – Iqra Braille Electronic; Braille codes; Android; Blind People.